Politik Hukum Pengelolaan Sumber Daya Air di Sumur Tujuh Cikajayaan Dalam Menjamin Hak Masyarakat Lokal - Iman Jalaludin Rifa’i; Haris Budiman; Erga Yuhandra; Mina Rabiatul Aisyah (Amsir Law Journal, 2025)
There are widespread conflicts over water resources management in Indonesia, such as in the case of Sumur Tujuh Cikajayaan which involved the community, government and private sector in fighting over water management rights. This research uses a normative juridical method with a conceptual, theoretical and statutory approach related to water resources. Regulations that prioritize economic interests often ignore the rights of local communities and developed local wisdom, creating disharmony between customary law and positive law. The research results show that weak community involvement and minimal integration of customary law cause ecological injustice in water management. Therefore, strategies are needed to strengthen the role of communities and harmonize customary law and positive law to realize fair and sustainable water management. ___ Referensi Books with an author: Marzuki, P. M. (2016). Penelitian Hukum, Jakarta: Kencana. Journal articles: Adnyani, N. K. S. (2021). Pengakuan Atas Kedudukan Dan Keberadaan Masyarakat Hukum Adat Kajian Pengaturan Subak Dalam Perspektif Hukum Negara. Jurnal Pendidikan Kewarganegaraan Undiksha, 9(2), 463-473. https://doi.org/10.23887/jpku.v9i2.34149 Ahmad, A., Pransisto, J., & Syahril, M. A. F. (2023). Perlindungan Hukum Terhadap Konsumen Dalam Transaksi E-Commerce. Jurnal Litigasi Amsir, 10(3), 222-232. https://journalstih.amsir.ac.id/index.php/julia/article/view/249 Alfitriani, A., Octavianty, O., Mutmainna, M., & Pransisto, J. (2022). Perlindungan Hukum Terhadap Konsumen Dalam Transaksi Jual-Beli Melalui E-Commerce. Jurnal Litigasi Amsir, 24-32. https://journalstih.amsir.ac.id/index.php/julia/article/view/174 Apriani, W., & Fikriana, A. (2023). Hukum Hak Asasi Manusia; Perspektif Internasional Tentang Kesenjangan Yang Perlu Disikapi. Al-Zayn: Jurnal Ilmu Sosial & Hukum, 1(1), 35-46. https://doi.org/10.61104/alz.v1i1.77 Asmaul, A., Karim, K., & Adhilia, L. T. F. (2023). Perlindungan Hukum Terhadap Pelanggaran Hak Cipta Melalui Internet. Jurnal Litigasi Amsir, 239-253. https://journalstih.amsir.ac.id/index.php/julia/article/view/254 Chandra, F., Diar, A., & Hartati, H. (2024). Konstitusi Hijau (Green Constitution) dalam Upaya Pelestarian Lingkungan Hidup yang Berkeadilan. Jurnal Penelitian Inovatif, 4(3), 889-896. https://doi.org/10.54082/jupin.441 Chandranegara, I. S. (2016). Purifikasi Konstitusional Sumber Daya Air Indonesia. Jurnal Rechts Vinding: Media Pembinaan Hukum Nasional, 5(3), 359-379. https://dx.doi.org/10.33331/rechtsvinding.v5i3.150 Cristiana, E., Jesica, J., & Yetno, A. (2023). Tinjauan atas undang-undang dan peraturan terkait pertambangan, sumber daya air, dan lingkungan hidup. Belom Bahadat, 13(2), 47-64. https://doi.org/10.33363/bb.v13i2.1037 Dewi, M. N. K., Miqat, N., & Purwanda, S. (2024). Analysis of the Legal Substance of Indonesia's Bilateral Investment Treaty (BIT): Balance of Rights and Obligations Based on National Interest. Pena Justisia: Media Komunikasi dan Kajian Hukum, 23(3), 3216-3232. https://doi.org/10.31941/pj.v23i3.5619 Dirkareshza, R., Novyana, H., Surahmad, S., & Nurhalizah, A. (2024). Penyelesaian Sengketa pada Masyarakat Hukum Adat Urug melalui Studi Etnografi. Jurnal Ilmiah Ilmu Sosial, 10(2), 218-226. https://doi.org/10.23887/jiis.v10i2.83772 Erfan, M., Pransisto, J., & Syahril, M. A. F. (2023). Perlindungan Hukum Bagi Konsumen dari Peredaran Makanan Kedaluwarsa. Jurnal Litigasi Amsir, 10(2), 94-107. https://journalstih.amsir.ac.id/index.php/julia/article/view/228 Fatristya, L. G. I., & Sarjan, M. (2024). Optimalisasi Kearifan Lokal dalam Pengelolaan Sumber Daya Alam dan Lingkungan di NTB: Literature Review. Kappa Journal, 8(3), 436-445. https://doi.org/10.29408/kpj.v8i3.28076 Galib, W. K., Irwan, A. L., Thaha, R., Prawitno, A., & Alfiani, N. (2024). Peran Pemerintah Daerah Dalam Penyediaan Air Bersih di Kota Makassar. Jurnal Pemerintahan dan Politik, 9(3), 220-227. https://doi.org/10.36982/jpg.v9i3.4391